2009
DOI: 10.1038/gt.2009.112
|View full text |Cite
|
Sign up to set email alerts
|

Plasmids encoding the mucosal chemokines CCL27 and CCL28 are effective adjuvants in eliciting antigen-specific immunity in vivo

Abstract: A hurdle facing DNA vaccine development is the ability to generate strong immune responses systemically and at local immune sites. We report a novel systemically administered DNA vaccination strategy using intramuscular codelivery of CCL27 or CCL28, which elicited elevated peripheral IFN-g and antigen-specific IgG while driving antigen-specific T-cell secretion of cytokine and antibody production in the gut-associated lymphoid tissue and lung. This strategy resulted in induction of long-lived antibody response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 53 publications
1
57
0
Order By: Relevance
“…Recent studies found that systemic immunization of animals with the CCR10 ligand CCL27 or CCL28 as an adjuvant increased titers of antigen-specific IgA antibodies in mucosal tissues such as intestines, suggesting that manipulating the CCR10/ligand axis could be useful in enhancing the vaccination efficacy against mucosal pathogens (28,29). It will be interesting to study how CCR10/ligands increase the mucosal IgA memory in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies found that systemic immunization of animals with the CCR10 ligand CCL27 or CCL28 as an adjuvant increased titers of antigen-specific IgA antibodies in mucosal tissues such as intestines, suggesting that manipulating the CCR10/ligand axis could be useful in enhancing the vaccination efficacy against mucosal pathogens (28,29). It will be interesting to study how CCR10/ligands increase the mucosal IgA memory in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we selected 5 peptide epitopes -KSFKDILPK (SAG1 224-232 ), STFWPCLLR (SAG2C [13][14][15][16][17][18][19][20][21] ), AVVSLLRLLK (GRA5 89-98 ), SSAYVFSVK (SRS52A 250-258 ), and AMLTAFFLR (GRA6 [164][165][166][167][168][169][170][171][172] ) -that elicited IFN-γ from peripheral blood mononuclear leukocytes (PBMCs) from T. gondii seropositive HLA-A03 supertype humans. SAG1 is a surface protein expressed in tachyzoites and mediates adhesion of the parasite to the host cell prior to invasion (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…The antitumor adjuvant effect of CCL21 was also demonstrated in a melanoma animal model (Yamano et al, 2006). In an influenza virus DNA vaccine study, we al-so observed that coinjection with chemokines, CCL27 and CCL28 induces long-lived viral neutralizing antibodies, leading to protection from morbidity and mortality associated from a lethal influenza virus challenge (Kutzler et al, 2009). Along with this, coinjection of HBsAg DNA vaccines with plasmid DNAs expressing CCL20 and a cytokine, Flt3 (fms-related tyrosine kinase 3) ligand induced Ag-specific immune responses in HBsAg transgenic mice by recovering DC functions (personal communication with Sidong Xiong), suggesting an important role of coinjection of certain chemokines and cytokines in overcoming Ag-specific immune tolerance.…”
Section: Cytokines and Chemokines As Adjuvantsmentioning
confidence: 89%